Role of Islamic microfinance in women's empowerment: Evidence from Rural Development Scheme of Islami Bank Bangladesh Limited - Md. Saiful Islam (ISRA International Journal of Islamic Finance, 2021)
Purpose - The purpose of this study is to investigate the impact of Islamic microfinance services (IMFS) on women's empowerment in rural Bangladesh. Design/methodology/approach - The study is based on a multi-stage sampling technique. The primary data are collected through a face-to-face survey of 389 women respondents who have received IMFS from the Islami Bank Bangladesh Limited. Cronbach's alpha test is conducted to test the reliability and internal consistency of collected data. Paired-sample tests, logit regression and proportion hypothesis tests are conducted to measure the impact of IMFS on women's empowerment. Descriptive and inferential statistics are used to interpret the data. Findings - The study reveals that IMFS have led to structural transformation in the occupation dynamics of the respondents' families from agriculture to retail businesses. IMFS have had a significant positive impact on household income, savings and expenditure; have improved standard of living and human capital formation; and have enhanced all three dimensions of empowerment, namely, economic empowerment (ECEM), socio-cultural empowerment (SCEM) and familial empowerment (FLEM). Of them, ECEM and SCEM have positively contributed toward overall women's empowerment, while FLEM has a negative but insignificant impact on overall empowerment. The respondents' perception also supports the finding that IMFS have benefited rural women and empowered them. Originality/value - The study is based on primary data. It leads to an inquiry as to whether women are dominant in familial affairs. If so, it may reduce the state of happiness and overall women's empowerment. There is a clear gap in the existing literature about this inquiry.
Keywords: 330; Economic empowerment; Familial empowerment; Islamic microfinance; Rural Bangladesh; Socio-cultural empowerment; Women's empowerment